General In Situ Photoactivation Route with IPCE over 80% toward CdS Photoanodes for Photoelectrochemical Applications. Issue 52 (1st November 2021) - Wang, Ying; Chen, Xiuyu; Xiu, Hao; Zhuang, Huanglong; Li, Jianming; Zhou, Yang; Liu, Deyu; Kuang, Yongbo
Abstract: Cost‐effective photoanodes with remarkable electronic properties are highly demanded for practical photoelectrochemical (PEC) water splitting. The ability to manipulate the surface carrier separation and recombination is pivotal for achieving high PEC performance for water splitting. Here, a facile and economical approach is reported for substantially improving the surface charge separation property of CdS photoanodes through in situ photoactivation, which significantly reduces surface charge recombination through the formation of thiosulfate ion which is favorable to the transfer of photogenerated holes and a uniform nanoporous morphology via the dissolving Cd 2+ with phosphate ions on the surface of CdS. The resulting CdS electrodes through scalable particle transfer method exhibit nearly tripled photocurrents, with an incident‐photon‐to‐current conversion efficiency (IPCE) at 480 nm exceeding 80% at 0.6 V versus reversible hydrogen electrode (RHE). And the CdS thin films prepared from chemical bath deposition display quadrupled photocurrents after the stir and PEC activation, with an IPCE of 91.7% at 455 nm and 0.6 V versus RHE. With the suppression of photocorrosion in alkaline borate buffer, the activated photoanodes show great stability for solar hydrogen production at the sacrifice of sulfite. This work brings insights into the design of nanoporous metal sulfide semiconductors for solar water splitting. Abstract : A facile yet powerful surface engineering strategy by in situ photoactivation is proposed to CdS photoanodes. This approach reduces surface charge recombination through the formation of thiosulfate ion and forms a uniform nanoporous morphology via dissolving Cd 2+ with phosphate ions on the surface. The resultant photoanodes present significantly prompted performance for photoelectrochemical application.